Ibn al-Jazzār's Zād al-musāfir wa-qūt al-ḥāḍir. Provisions for the Traveller and Nourishment for the Sedentary : Books III, IV, and V: Diseases of the Internal Organs - Bos, Gerrit,; Käs, Fabian, (Islamic History and Civilization ;, 2026)
The medical compendium entitled Zād al-musāfir wa-qūt al-ḥāḍir (Provisions for the Traveller and Nourishment for the Sedentary) and compiled by Ibn al-Jazzār from Qayrawān in the tenth century is one of the most influential handbooks in the history of western medicine. In the Middle Ages, it was translated into Latin and Byzantine Greek, as well as three times into Hebrew. The present volume - being the last in a series of books published since the 1990ies - includes a new critical edition of the Arabic text of books III through V dealing with diseases of the internal organs along with an annotated English translation.